2011
DOI: 10.1002/ejoc.201100613
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable Tertiary Amine Modified Diarylprolinol Ether as Aminocatalyst for the Sequential Asymmetric Synthesis of Functionalized Cyclohexanes and Chromenes

Abstract: The one-pot, organocatalytic Hayashi sequential reaction (HSR) of β-nitroacrylate, aldehyde, toluenethiol, and ethyl 2-(diethoxyphosphoryl)acrylate allowed the synthesis of almost stereoisomerically pure, highly functionalized polysubstituted cyclohexanes with very high diastereo-and enantioselectivity (up to Ͼ 99 % ee). The one-pot synthesis consists of the tertiary amine modified diarylprolinol silyl ether-mediated asymmetric Michael reaction, a domino Michael reaction/Horner-Wadsworth-Emmons reaction, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 107 publications
0
9
0
Order By: Relevance
“…The functionalization of the vinylphosphonates under various reaction conditions provides access to versatile phosphorus-containing synthetic intermediates . Such transformations include the Michael addition reactions (aza-, sulfa-, and oxa-Michael addition reactions), Diels–Alder reaction, epoxidations, aminohydroxylation, dihydroxylation, aziridination, Heck reaction, ene reaction, and cross-metathesis reactions . In addition, vinylphosphonate derivatives have also shown significant biological activities: they have been extensively explored for anticancer, , antiviral, , and antibacterial applications .…”
Section: Introductionmentioning
confidence: 99%
“…The functionalization of the vinylphosphonates under various reaction conditions provides access to versatile phosphorus-containing synthetic intermediates . Such transformations include the Michael addition reactions (aza-, sulfa-, and oxa-Michael addition reactions), Diels–Alder reaction, epoxidations, aminohydroxylation, dihydroxylation, aziridination, Heck reaction, ene reaction, and cross-metathesis reactions . In addition, vinylphosphonate derivatives have also shown significant biological activities: they have been extensively explored for anticancer, , antiviral, , and antibacterial applications .…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, Xu and coworkers developed a novel tertiary amine‐modified diarylprolinol silyl ether 4 c , which, relatively, facilitated the oxa‐Michael‐adol reaction of 1 and 2 , resulting 2 H ‐flavenes with moderate to good enantioselectivities (Scheme ) . Although the steric difference between ( R )‐ 4 a and 4 c was subtle, the authors believed that the electronic effect of the tertiary amine groups of 4 c enhanced the enantioselective activity of the chiral seconary amine, leading to a better result.…”
Section: Asymmetric Synthesis Of 2h‐flavenesmentioning
confidence: 99%
“…Very recently, Xu et al [46] reported an improved protocol for the domino-oxa-Michael reaction of salicylaldehydes 1 with α,β-unsaturated aldehydes 2 employing tertiary amine-modified diarylpyrrolinol-TMS ether III as a water-soluble and recyclable organocatalyst with 4-chlorobenzoic acid as cocatalyst (Scheme 5) for the synthesis of 2 H -chromene derivatives 3 . The electronic effect of the tertiary amine group in the modified catalyst was believed to enhance the enantioselectivity of the chiral secondary amine.…”
Section: Reviewmentioning
confidence: 99%